Estimating disparities in the treatment of foreign nationals in the criminal justice process in the Czech Republic - Vávra, Jan; Dušek, Libor; Kovanda, Lukáš, 1980-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2016)
This thesis examines the effect of foreign nationality on the outcomes of criminal process in the Czech Republic. Foreign citizens are overrepresented by 2% compared to their share in population in all stages of the criminal process, suggesting possible discrimination by domestic authorities. Using rich case level datasets from 2005 to 2015 observed gaps are decomposed to part explained by a difference in the objective characteristics of the cases and unexplained part, suggesting possible inequality of treatment. Foreigner gaps in probability of charge, probability of conviction, probability of imprisonment, length of the sentence and probability of release from prison on parole are decomposed. Majority of observed disparities in the outcomes can be attributed to higher involvement of foreigners in more serious crimes compared to nationals. Unexplained disparities remain in probability of imprisonment and probability of release on parole, suggesting possible unequal treatment in these two outcomes.
Vedoucí práce: Libor Dušek
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2016
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2016
Způsob přístupu: Internet
Keywords: ekonomická analýza [obor dipl. práce]; diplomové práce; master's theses